Disease complexity: A bird’s eye view - Lahiri, Chandrajit * (2015)
Over the last few decades, biologists understood gradually that a set of complex interactions between the numerous constituents of a cell, gives rise to different biological phenotypes. Diseases serve as interesting examples of a great number of heterogeneous, interacting entities of biological systems. Though the ultimate goal is to understand the causes and effects along with the mechanisms of regulation, the precise simulation to mimic the real biological phenomena had been quite tough. The present talk encompasses a discussion on the model networks of few infectious diseases focused around identifying the proteins indispensable for virulence followed by probing into the structure function relation of the proteins involved there in and their molecular evolution. The diseases are either caused by bacterial infection like typhoid caused by Samonella enterica, nosocomial infection by Acinetobacter baumannii and fish pathogenesis by Edwardsiella tarda. On an initial note, the indispensability issue has been taken off for virulent proteins from the 28 Pathogenicity Alien Islands (PAI) causing the hospital borne infection caused by Acinetobacter. Taking down to the practical level, a conglomerate of secretion systems and signaling proteins of Edwardsiella were used for identifying an important candidate suitable for fish vaccination. Finally, a methodology has been figured out theoretically to focus on the indispensable virulent proteins amongst a barrage of Salmonella Pathogenecity Island (SPI) proteins and proven by microarray data for Salmonella. The candidate for therapeutic drug targeting had also been modeled. An overview of phylogenetic network brought out some sources of evolution.